Simultaneous recordings of oesophageal acid exposure with conventional pH monitoring and a wireless system (Bravo). Issue 12 (20th April 2005) - des Varannes, S Bruley; Mion, F; Ducrotté, P; Zerbib, F; Denis, P; Ponchon, T; Thibault, R; Galmiche, J P
Abstract : Objectives: Oesophageal pH monitoring is a useful test for the diagnosis of gastro-oesophageal reflux disease (GORD) but has some limitations related to the nasopharyngeal electrode. Recently, a telemetric catheter free system (CFS) (Bravo; Medtronic) was developed. The aim of this study was to determine the concordance of data between the conventional pH measurement system (CPHMS) and the CFS Bravo. Methods: Forty patients with symptoms suggestive of GORD underwent 24 hour oesophageal pH monitoring using the CPHMS with a nasopharyngeal electrode and the Bravo CFS simultaneously. The sensitive tips of both electrodes were positioned at the same level under fluoroscopy. In addition to automatic analysis, each reflux episode was checked visually and characterised. Results: There was a significant correlation ( r  = 0.87, p<0.0001) between the 24 hour oesophageal acid exposures recorded by the CPHMS and the CFS. Twenty four hour oesophageal acid exposure was significantly lower with the CFS than with the CPHMS (2.4 (0.4–8.7) v 3.6 (0.7–8.6); p< 0.0001). Consequently, with the CFS, the cut off level for the diagnosis of GORD, as calculated from the regression equation, was 2.9% (for the 4.2% cut off determined in controls with the CPHMS). After this adjustment, concordance of the diagnosis of GORD was 88% (kappa 0.760). Diagnosis of GORD was established in more patients with the CFS 48 hour results than with the 24 hour results. Conclusions: Despite strong correlations between oesophageal acid exposure recorded with the two devices, the Bravo CFS significantly under recorded acid exposure compared with the CPHMS. Provided some correcting factors are used, the Bravo CFS can improve the sensitivity of pHmetry for the diagnosis of GORD by allowing more prolonged recordings.